Activation and Role of Astrocytes in Ischemic Stroke - Shen, Xin-Ya; Gao, Zhen-Kun; Han, Yu; Yuan, Mei; Guo, Yi-Sha; Bi, Xia (Frontiers in Cellular Neuroscience, 2021)
Ischemic stroke refers to the disorder of blood supply of local brain tissue caused by various reasons. It has high morbidity and mortality worldwide. Astrocytes are the most abundant glial cells in the central nervous system（CNS）. They are responsible for the homeostasis, nutrition and protection of the CNS, and play an important role in the physiological and pathological processes of many nervous system diseases. After stroke injury, astrocytes are activated and play a protective role through the heterogeneous and gradual changes of their gene expression, morphology and proliferation and function, that is reactive astrocytes. However, the function of reactive astrocytes has always been a controversial topic. A large number of studies have shown that reactive astrocytes are a double-edged sword, which have both beneficial and harmful effects. It is worth noting that astrocytes' various functions are determined by their different spatial and temporal expression. Here, we comprehensively review the different roles and mechanisms of astrocytes after ischemic stroke. In addition, the intracellular mechanism of astrocyte activation has also been involved. More importantly, due to the complex cascade reaction and action mechanism after ischemic stroke, the role of astrocytes is still difficult to define, but there is no doubt that astrocytes are one of the key factors mediating the deterioration or improvement of ischemic stroke.